Determinants of tuberculosis treatment adherence through information, motivation, and behavioural skills: a study of TB patients in Serdang Bedagai - Nixson Manurung; Sarida Surya Manurung; Rostinah Manurung (Intelektual Pustaka Media Utama, 2026)
Patient non-compliance in undergoing treatment can increase the risk of therapy failure, transmission, and drug resistance. To analyse the treatment adherence strategies of tuberculosis patients through the information, motivation, behavioural skills (IMB) approach. The research uses a quantitative approach with a cross-sectional design. The research sample consists of tuberculosis patients in Serdang Bedagai Regency who were selected using the cluster random sampling technique at several community health centers. Data were collected using a questionnaire based on the variables of information, motivation, and behavioural skills, and then analysed by using structural equation modelling (SEM). The indicators of non-compliance are divided into three main components. The information component includes understanding tuberculosis, increasing nutritional intake, and cough and sneeze etiquette; the motivation component includes exercise and sunbathing, social interaction, and family support; the behavioural skill component includes regular control, mask use, sputum disposal etiquette, and medication schedules. The main findings indicate that information and motivation influence behavioural skills, with the impact of information being stronger than that of motivation. This study concludes that the IMB approach can be used as a basis for strategies to improve medication adherence among tuberculosis patients through the reinforcement of accurate information, sustained motivation, and the formation of regular medication behaviour.